Standar Ganda Penyidik dalam Menerapkan Diskresi Bagi Pelaku Tindak Pidana Pornografi di Internet (Jurnal Legislatif, 2021)
AbstractReferring to Article 24 Paragraph (1) of the Criminal Procedure Law (KUHAP), detention is imposed on criminal suspects with criminal threats over 5 (five) years. However, on the basis of discretion authority of the police, the police in granting detention for pornography crimes with criminal threats over 5 (five) years, often acting outside of the provisions of applicable laws and regulations. Discretion is actually a long process, which boils down to the final result of taking the act. Decisions on the use of discretionary authority need to be reviewed starting from the beginning of the decision-making process of the use of the board of directors, namely the basis of the investigation. To find out, paradigmatic studies try to elaborate in more detail, refine, and clearly. The difference gradations will be shown to the level of ontology, epistemology, and methodology. The findings will explain that the investigator's understanding of discretion and its application is influenced by the paradigm that overshadows it.Keywords: Detentio;.Discretion; Paradigm; Pornographic.Abstrak Merujuk Pasal 24 Ayat (1) Kitab Undang-Undang Hukum Acara Pidana (KUHAP), penahanan dikenakan terhadap tersangka tindak pidana dengan ancaman pidana di atas 5 (lima) tahun. Namun, atas dasar kewenangannya, kepolisian seringkali bertindak di luar dari ketentuan peraturan perundang-undangan yang berlaku. Keputusan penggunaan kewenangannya tersebut perlu ditelaah mulai dari awal proses penentuan keputusan penggunaan kewenangannya tersebut, yaitu dasar pemikirian para penyidik. Untuk mengetahuinya, telaah paradigmatik mencoba menguraikan secara lebih rinci, halus, dan jelas. Gradasi perbedaan akan diperlihatkan hingga tataran ontologi, epistemologi, dan metodologinya. Penelitian ini menggunakan tradisi penelitian kualitatif dengan metode penelitian normatif dan pendekatan hukum komparatif. Hasil temuan akan menjelaskan bahwa pemahaman penyidik mengenai diskresi dan penerapannya dipengaruhi oleh paradigma yang menaunginya.Kata Kunci: Diskresi; Paradigma; Penahanan;.Pornografi.